(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate new and current inflammatory markers in women with polycystic ovary syndrome (PCOS) and to clarify the role of these markers in the etiopathogenesis of PCOS.Material and Methods: This retrospective study included 97 women with PCOS and 124 body mass index-matched controls without PCOS. The parameters examined as new and current markers in both groups were the monocyte-to-high density lipoprotein cholesterol (HDL-C) ratio, high sensitivity C-reactive protein/ albumin ratio, systemic immune-inflammation index, inflammatory prognostic index, prognostic nutritional index, white blood cell count, mean platelet volume, platelet distribution width, plateletcrit, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, triglycerides to HDL-C ratio and the lipid accumulation product index.Results: No significant difference was found between the PCOS and control group in respect of inflammatory markers. The age and follicle-stimulating hormone values of PCOS patients were found to be lower than those of the control group. Luteinizing hormone, free androgen index, insulin and the homeostasis model assessment of insulin resistance values of PCOS patients were significantly higher than those of the control group.Conclusion: In terms of inflammatory parameters, no significant difference was determined between patients with PCOS and the control group. Chronic inflammation may be multifactorial in PCOS and there is a need for studies with larger sample sizes to be able to explain the exact role of inflammatory markers in PCOS etiology.Keywords: Polycystic ovary syndrome; inflammation; inflammatory markers